"Fear guides the eyes of the beholder": Assessing gaze avoidance in social anxiety disorder via covert eye tracking of dynamic social stimuli. (June 2019) - Weeks, Justin W.; Howell, Ashley N.; Srivastav, Akanksha; Goldin, Philippe R.
Highlights: Gaze avoidance in social anxiety disorder (SAD) examined using covert eye-tracking. Tracked gaze to video feedback stimuli per bivalent fear of evaluation (BFOE) model. Fears of positive and negative evaluation related to state anxiety during stimuli. SAD participants showed reduced eye gaze during both positive and negative stimuli. Gaze avoidance is a biobehavioral marker of SAD and supports the BFOE model. Abstract: Gaze avoidance is an important feature of social anxiety disorder (SAD) and may serve as a biobehavioral marker of SAD. The purpose of the present study was to replicate and extend findings on gaze avoidance in SAD via eye tracking during a computerized social simulation. Patients with SAD ( n = 27) and a (sub)sample of demographically-matched healthy controls (HC; n = 22) completed a computerized, dynamic social simulation task involving video clips of actors giving positive and negative social feedback to the participant. All participants were unknowingly eye tracked during the simulation, and post-study consent was obtained to examine responses. Consistent with the bivalent fear of evaluation (BFOE) model of social anxiety, fear of positive evaluation related systematically to state anxiety in response to positive social feedback, and fear of negative evaluation related systematically to state anxiety in response to negative social feedback. Moreover, compared to HCs, SAD patients exhibited significantly greater global gaze avoidance in response to both the positive and negative video clips. Our results provide strong additional support for gaze avoidance as a biobehavioral marker of SAD, as well as additional support for the BFOE model. Implications for the assessment and treatment of SAD are discussed.